ANALISIS NILAI-NILAI MORAL DALAM NOVEL “KEMBANG TURI” KARYA BUDI SARDJONO - Maguna Eliastuti (Jurnal Genta Mulia, 2017)
The aim of this research is to reveal the moral values in the novel "Kembang Turi" and the author hopes that readers can understand the contents of the novel. The method used in analyzing this novel is by using a bibliographic method which contains two elements of the novel's value, namely intrinsic and extrinsic elements. Apart from that, the author also uses a descriptive method with an approachmoral. After the author analyzes the novel "Kembang Turi" in terms of moral aspects, the author can draw interest conclusion that there are positive and negative aspects to the main characters, Dirman, Marni and Manaf. For aspects Negatives are advised not to be emulated but for our knowledge in social life.